Allergenicity assessment of fungal species using immunoclinical and proteomic techniques: a study on Fusarium lateritium. Issue 5 (2nd September 2020) - Dey, Debarati; Gupta Bhattacharya, Swati
ABSTRACT: Airborne fungal spores are extensively reported as the elicitors of respiratory allergies in human. Fusarium lateritium is one such fungal species reported for eliciting significant skin prick results from India. The present study aims to analyze the allergenic potential of F. lateritium followed by the identification of allergens. The total protein of F. lateritium was subjected to 1dimensional (1D) and 2D gel electrophoresis followed by corresponding IgE-specific immunoblots. We found 8 immunoreactive bands/zones in (1D) immunoblot using 11 F. lateritium -sensitised patient sera. In 1D immunoblot, a 34 kDa band was detected in >80% of the patients and hence considered as a potential allergen of F. lateritium . Corresponding 34 kDa spot in 2D-immunoblot was analyzed by mass spectrometric analysis and identified as Glyceraldehyde 3-phosphate dehydrogenase. The identified F. lateritium allergen holds the potential to instigate vaccine development for immunotherapy of F. lateritium sensitized patients.